Sovereign Debt Restructurings in Belize : Achievements and Challenges Ahead - Asonuma, Tamon; Peraza, Gerardo; Tsuda, Takahiro; Vitola, Kristine (Washington, D.C. : International Monetary Fund, 2014)
This paper examines the causes, processes, and outcomes of the two Belize sovereign debt restructurings in 2006-07 and in 2012-13 that occurred outside of an IMF-supported program. It finds that the motivation for the two debt restructurings differed, as the former was driven by external liquidity concerns while the latter was motivated by a substantial increase in the coupon rates and future fiscal solvency concerns. Despite differential treatment between residents and non-residents, both 2006-07 and 2012-13 debt exchanges were executed through collaborative engagement, due in part to the existence of a broad-based creditor committee and the authorities' effective communication strategy. However, while providing temporary liquidity relief, neither of the debt restructurings properly addressed long-term debt sustainability concerns. Going forward, the success of the 2012-13 debt restructuring will still depend on the country's ability to strengthen fiscal efforts and public debt management framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet